Thermal history of the southern Central Cordillera and its exhumation record in the Cenozoic deposits of the Upper Magdalena Valley, Colombia. (April 2021) - Villamizar-Escalante, N.; Bernet, M.; Urueña-Suárez, C.; Hernández-González, J.S.; Terraza-Melo, R.; Roncancio, J.; Muñoz-Rocha, J.A.; Peña-Urueña, M.L.; Amaya, S.; Piraquive, A.
Abstract: The roughly 600 km long Central Cordillera of Colombia shows a varied tectonic, magmatic, and exhumation history, despite the reasonably homogenous appearance concerning topography, outcropping lithologies, and strike. Here we show with new geo-thermochronological data the thermal evolution of the southern Central Cordillera since the Early Jurassic. Extensive Jurassic magmatism is recorded by U–Pb crystallization ages of arc plutons intruded by dike swarms and collateral volcaniclastic flows. Inverse modeling of zircon and apatite fission-track ages from Central Cordillera reveals a long period of slow cooling since the Early Cretaceous at rates of 2–3 °C/Myr, based on best-fit t-T path solutions. The Early Cretaceous phase is recorded by the cooling of Jurassic granitoids, most likely driven by slow erosional exhumation along the western flank of the Central Cordillera related to the collision and accretion of the Quebradagrande arc against the continental margin. The Late Cretaceous rapid exhumation event caused by the ~80-70 Ma collision and accretion of the Caribbean Large Igneous Province at the western margin of South America observed in other parts of the Central Cordillera, is not detectable in our study area . During the Eocene-Oligocene (ca. 45-31 Ma), the obtained time-temperature paths are compatible with slow cooling rates between 1 and 2 °C/Myr and slow exhumation at long-term average rates of about 0.1 km/Myr. The combination of geo-thermochronological data and petrology of clastic basin sediments presented in this study indicates that the unroofing of the southern Central Cordillera crystalline basement also occurred during the Eocene-Oligocene phase of the Andean Orogeny, as widely recognized by a major unconformity. The exhumation was coeval with the reactivation of crustal structures, such as the Plata-Chusma fault, as evidenced by the syn-tectonic deposits of the Gualanday Group. Graphical abstract: Image 1 Highlights: Slow monotonic cooling of the southern Central Cordillera. Provenance analysis of Gualanday Group (U–Pb & Fission-track). Compositional shift due unroofing of the Central Cordillera. Plata-Chusma fault activity.